Perbandingan Kinerja Keuangan Perusahaan Manufaktur Sub Sektor Pertambangan di Indonesia : (Studi pada PT Adaro Energy Indonesia TBK dan PT Batulicin Nusantara Maritim TBK 2019-2023) - Salsabila Maulidya Supriadi Bahrim; Dwi Dita Ratnasari; Cholis Hidayati (Manajemen Kreatif Jurnal, 2024)
This study aims to analyze and compare the financial performance of two manufacturing companies in the mining sub-sector in Indonesia, namely PT Adaro Energy Indonesia Tbk and PT Batulicin Nusantara Maritim Tbk during the period 2019-2023. The analysis was carried out using financial ratios including liquidity, operational efficiency, solvency, and profitability. The results of the study indicate that PT Adaro Energy Indonesia Tbk has better financial performance than PT Batulicin Nusantara Maritim Tbk. PT Adaro Energy Indonesia Tbk excels in the stability of the current ratio which is consistently above the safe limit, reflecting the company’s ability to meet short-term obligations. In addition, operational efficiency is demonstrated through fast inventory turnover, effective management of receivables, and optimization of the use of fixed assets, all of which contribute to increased cash flow and revenue. These findings indicate the importance of good financial management to support the sustainability and competitiveness of companies in the mining sector.